# Percent of Increase: 60 to 93 {(93-60)/60}x100=(?). 60 to 93 percent increase provides the comprehensive information on how to find what is the percent of increase from 60 to 93.

60 to 93 percent increase:
(93 - 60)/60 x 100 = (?)
= 33/60 x 100
= 55%
(93 - 60)/60 x 100 = 55%
Hence,
the percent of increase from 60 to 93 is 55%

where,
60 is the base or reference quantity,
93 is the relative or increased quantity,
33 is the difference between base and increased quantity,
55% is the percent increase.

## How-to: What is the percent of increase from 60 to 93?

The result of difference between the increased quantity 93 and reference quantity 60 divided by the reference quantity 60, multiplied with 100 is the percent of increase from 60 to 93. The below is the step-by-step work shows how to find what is the percent of increase from 60 to 93 by using the mathematical formula. step 1 Observe the input parameters, values and what to be found:

Input values:
Base or reference value X = 60
Increased or relative value Y = 93

What to be found:
Find the percent increase from 60 to 93.
(93 - 60)/60 x 100 = (?)%

step 2 Find the difference between increased quantity 93 and reference quantity 60:
93 - 60 = 33

step 3 Divide the difference 33 by the reference quantity 60, and multiply the result with 100:
33/60 x 100 = 55%

Hence,
55% is the percent of increase from 60 to 93. 